Understanding social work research - Hugh Mclaughlin (New Delhi Sage Publications, 2025)
Paperback. Condition: Very Good. 'An excellent introductory textbook for social work students that effectively links social work theories and concepts to research' - Vivienne Barnes, Coventry University This excellent new textbook offers a comprehensive introduction to the nature of social work research. The book clearly demonstrates how research-mindedness is key to improving individual and collective social work practice, helping practitioners to effectively navigate the complex issues they face on a daily basis. The book satisfies the curriculum benchmarks for social work training and considers research in relation to a number of important social work themes, including ethics, anti-oppressive practice, service user research, evidence-based practice and interdisciplinary work. The book will help readers: " critically reflect on their own social work practice " assess, appraise and apply research " effectively advocate on behalf of service-users " confidently engage in debates about the profession " reflect on legislative and policy developments .Understanding Social Work Research is clear and accessible, containing reflective questions and practice examples illustrating the links between research and social work practice. This book will be essential reading for all social work trainees and will provide invaluable support for postgraduate students and practitioners wishing to consolidate their understanding of social work research. Hugh McLaughlin is the Director of Social Work and Social Policy at Salford University. The book has been read but is in excellent condition. Pages are intact and not marred by notes or highlighting. The spine remains undamaged.
Keywords: Social Work